Clinical characteristics of Japanese patients with axial spondyloarthritis, and short-term efficacy of adalimumab - Otsuka, Akiyo (J Orthop Sci, 2015)
BACKGROUND: Ankylosing spondylitis (AS) is rarer in Japan than in Europe, probably because the European criteria, not well known by Japanese general physicians, regard AS as a progressive stage of axial spondyloarthritis (SpA). HLA-B27 is an important diagnostic marker of SpA; however, the incidence of the HLA-B27 allele is as low as 0.4 % in Japan. For Japanese SpA patients, other HLA alleles and clinical findings are required for earlier definitive diagnosis, for determining appropriate treatment timing, and for disease monitoring. METHODS: We investigated the HLA-B alleles of 36 patients clinically diagnosed with SpA. For 8 axial SpA patients we evaluated the short-term efficacy of subcutaneous adalimumab injections (40 mg every other week for ≥11 months). Treatment efficacy was evaluated by use of the Bath Ankylosing Spondylitis Activity Index (BASDAI) score, and serum TNF-α and IL-6 levels were measured pre and post-treatment. RESULTS: Among the 36 Japanese SpA patients, the HLA-B27 allele occurred infrequently (5.6 %) whereas the HLA-B44 and 61 alleles were the most frequently detected (25.0 %). We also detected severe bamboo spine on radiography in the absence of the HLA-B27 allele. All 8 patients with axial SpA experienced significant symptom improvement after adalimumab treatment; the HLA-B27 allele was absent from these patients. Serum TNF-α and IL-6 levels were elevated in cases with remarkable inflammatory pain and high disease activity. These cytokines decreased after therapy, however. Most patients with normal cytokine levels at baseline retained these low levels. CONCLUSIONS: The findings reveal the short-term efficacy of adalimumab. The remarkably low incidence of HLA-B27 among our patients indicates that HLA-B distribution is different from that in other countries. Serum TNF-α and IL-6 levels were not effective as biomarkers for cases without high disease activity, and further research with larger samples is needed. The efficacy of TNF blockers, however, suggested a potential localized TNF effect was present among SpA patients.